New records of marine fishes illustrate the biogeographic importance of Christmas Island, Indian Ocean - Hobbs, Jean-Paul; Ayling, A.; Choat, J.; Gilligan, J.; McDonald, C.; Neilson, J.; Newman, S. (Magnolia Press, 2010)
Christmas Island is situated in the tropical eastern Indian Ocean on a biogeographic border where Indian and Pacific Ocean faunas meet. Detailed field studies in 2004, 2007 and 2008, of the island’s fish fauna revealed 30 new records from 15 families. For six families (Dasyatidae, Chanidae, Bramidae, Mugilidae, Siganidae, Molidae) this is the first time a species has been recorded at Christmas Island. Many of the newly recorded fishes appear to have recently colonised the island, and establishing populations will be dependent on the availability of suitable habitat and conspecific mates. These new records illustrate that Christmas Island is important for range expansion because it serves as a critical stepping-stone in the dispersal of Pacific Ocean species into the Indian Ocean and vice versa. Contact between Indian and Pacific Ocean sister species has also resulted in hybridisation at Christmas Island.